Os animais na epistemologia naturalista de David Hume: uma leitura Darwiniana - Santos, Rubens Sotero dos (2019)
David Hume showed in the section on the reason of animals that nonhuman animals, like humans, reason causally. From this, we will defend the hypothesis that the argument by analogy, the strongest that Hume had and that led him to this thesis, is well-founded by him, corroborated by Charles Darwin´s evolutionary theory in that it defends a common ancestral of the species and, therefore, that there is a continuity or gradation among beings. We show´ll from this ancestry that the similarities, essential to the analogy, between men and animals which Hume observed, are sufficiently explained by evolution.